God's wounded world: American Evangelicals and the challenge of environmentalism - Gish, Melanie (Baylor University Press, 2020)
Cover -- Half-title Page, Title Page, Copyright, Dedication -- Contents -- Preface and Acknowledgments -- Abbreviations -- Introduction: An Unlikely Alternative -- 1. Evangelicalism and Environmentalism: A Contextualizing Overview -- 2. Theology First!: The Beginnings of Green Evangelicalism -- 3. Pioneer Creation Care Organizations -- 4. Politically Unafraid Evangelical Environmental Organizations -- 5. Organized Evangelical Environmental Skepticism -- 6. Apolitical Creation Care Organizations -- Conclusion: In the Middle but Not Necessarily of It -- Appendix -- Notes -- Bibliography -- Index.